Exact Solution to the Extended Zwanzig Model for Quasi-Sigmoidal Chemically Induced Denaturation Profiles: Specific Heat and Configurational Entropy. (23rd January 2014) - Aguilar-Pineda, G. E.; Olivares-Quiroz, L.
Abstract : Temperature and chemically induced denaturation comprise two of the most characteristic mechanisms to achieve the passage from the native stateN to any of the unstructured statesD j in the denatured ensemble in proteins and peptides. In this work we present a full analytical solution for the configurational partition function𝒵 q s of a homopolymer chain poly-X in the extended Zwanzig model (EZM) for a quasisigmoidal denaturation profile. This solution is built up from an EZM exact solution in the case where the fractionα of native contacts follows exact linear dependence on denaturant's concentrationζ ; thus an analytical solution for𝒵 L in the case of an exact linear denaturation profile is also provided. A recently established connection between the numberν of potential nonnative conformations per residue and temperature-independent helical propensityω complements the model in order to identify specific proteinogenic poly-X chains, where X represents any of the twenty naturally occurring aminoacid residues. From𝒵 q s, equilibrium thermodynamic potentials like entropy𝒮 and average internal energy〈E〉 and thermodynamic susceptibilities like specific heatC 𝓋 are calculated for poly-valine (poly-V) and poly-alanine (poly-A) chains. The influence of the rate at which native contacts denature as function ofζ on thermodynamic stability is also discussed.